T3 Type 2 diabetic hearts are energetically defective both globally and at the level of the mitochondria. (26th October 2016) - Kerr, M; Fialho, MS; Tyler, D; Heather, LC
Abstract : Introduction: Cardiac metabolism in type 2 diabetes is abnormal, with increased fatty acid oxidation, and decreased glucose oxidation. The ratio of phosphocreatine/adenosine triphosphate (PCr/ATP) is decreased in the hearts of diabetic patients, indicating an energetic defect. However, an underlying mechanism is yet to be determined. Methods: Diabetic and control hearts were perfused in an 11.7T magnet and high energy phosphates measured in contracting hearts via magnetic resonance spectroscopy. Cardiac subsarcolemmal (SSM) and interfibrillar (IFM) mitochondria were isolated from different diabetic and control rats, and respired using an oxygen-sensitive electrode with glutamate, pyruvate, malate (GPM), and fatty acids. Results: Diabetic hearts had a 20% reduction in ATP levels with no change in phosphocreatine. Despite this, cardiac function was unaltered between groups. Citrate synthase assay data, and mtDNA copy number showed that diabetic hearts have 30% more mitochondria than control heart. However, both SSM and IFM from diabetic rats had decreased respiratory rates when respired solely on GPM (normalised to mitochondrial protein), which was rescued by the addition of fats. Addition of palmitoyl-CoA (P-CoA) to GPM resulted in a 50% decrease in respiration in both diabetic and control mitochondria. Suppression was prevented if P-CoA was co-infused with carnitine, or if palmitoyl-carnitine was used. Inhibition from P-CoA was abolished in the presence of an uncoupling agent (FCCP), demonstrating inhibition was mediated via the phosphorylation apparatus. Conclusion: Diabetic hearts are energetically impaired when compared to control hearts. This energetic defect pairs with a mitochondrial defect, with diabetic hearts potentially compensating by increasing mitochondrial number.